RANCANG BANGUN SISTEM INFORMASI MAGANG DAN KERJA PRAKTIK FAKULTAS ILMU KOMPUTER UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Muhammad Rafi Pandya Pangestu (2021)
Job Training is a compulsory program for all students of the Faculty of Computer Science, Universitas Pembangunan Veteran Jakarta (FIK UPNVJ). This activity aims to help students get to know the work environment better, and to help students implement the results of the studies they have undertaken during lectures by practicing directly in the related agencies / companies. To take part in the practical lecture program, there are several processes such as registration, making licensing letters, selecting supervisors, selecting companies to conduct practical work courses, but currently the process is taking a long time and is less effective. Making this system aims to facilitate academic staff, lecturers and students in viewing data related to practical work lectures using the waterfall method. This system helps students especially in finding various references and methods as references in carrying out practical work courses. This system is designed in the form of a website which uses several tools such as Adobe XD, XAMPP, PhpMyadmin, MySql, Sublime Text. Then used several programming languages such as HTML, CSS, PHP, Javascript with the Bootstrap framework and Codeigniter. This system generates internships or practical work lectures based on data from students who have carried out KKP with details of KKP reports, methods used, and products / systems produced and information is also provided about companies / agencies that open jobs to conduct practical work lectures. Keyword: Job Training, Waterfall, Website, System.